Để \(f\left(x\right)=x^2-2mx+3m-2>0\) \(\forall x< 4\) thì:
\(\left[{}\begin{matrix}\Delta'< 0\\\left\{{}\begin{matrix}\Delta'=0\\\frac{-b}{2a}\ge4\end{matrix}\right.\\\left\{{}\begin{matrix}\Delta'>0\\4< x_1< x_2\end{matrix}\right.\end{matrix}\right.\)
TH1: \(\Delta'< 0\Rightarrow m^2-3m+2< 0\Rightarrow1< m< 2\)
TH2: \(\left\{{}\begin{matrix}\Delta'=0\\\frac{-b}{2a}\ge4\end{matrix}\right.\) \(\Rightarrow\left\{{}\begin{matrix}m^2-3m+2=0\\m\ge4\end{matrix}\right.\) \(\Rightarrow\) ko tồn tại m thỏa mãn
TH3: \(\left\{{}\begin{matrix}\Delta'>0\\4< x_1< x_2\end{matrix}\right.\) \(\Leftrightarrow\left\{{}\begin{matrix}\Delta'>0\\a.f\left(4\right)>0\\\frac{S}{2}>4\end{matrix}\right.\) \(\Leftrightarrow\left\{{}\begin{matrix}m^2-3m+2>0\\16-8m+3m-2>0\\m>4\end{matrix}\right.\)
\(\Rightarrow\) ko có m thỏa mãn
Vậy với \(1< m< 2\) thì \(f\left(x\right)>0\) \(\forall x< 4\)